The Notion Of The Intercultural Garden In Hungarian Context - Fáczányi, Zsuzsanna; Balogh, Péter István (4D Journal of Landscape Architecture and Garden Art, 2015)
The theory and practice of the urban community garden is becoming better known in Hungary too. In these gardens there is less emphasis on quantitative production than on environmentally conscious urban living, community experience or the demand for nature. Its purpose and social background are multifold. The intercultural garden is a type of community garden that offer the enjoy of food production and the proximity of earth and nature, as a social instrument helps the formation of interwoven communities and the connection of immigrants, refugees, urban minorities and of those who practice an unharboured culture. It is our firm belief that the intercultural garden type has a place and a social ground in the Hungarian urban environment, thus our goal is to familiarize users and shapers of Hungarian cities with its operation, consider the questions of its implementation by analysis, and also to determine its Hungarian definition.
Keywords: Intercultural Garden; Community Experience; Hungarian Urban Environment